2008
DOI: 10.1007/s00253-008-1410-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant/microbe cooperation for electricity generation in a rice paddy field

Abstract: Soils are rich in organics, particularly those that support growth of plants. These organics are possible sources of sustainable energy, and a microbial fuel cell (MFC) system can potentially be used for this purpose. Here, we report the application of an MFC system to electricity generation in a rice paddy field. In our system, graphite felt electrodes were used; an anode was set in the rice rhizosphere, and a cathode was in the flooded water above the rhizosphere. It was observed that electricity generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
158
4
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(176 citation statements)
references
References 23 publications
8
158
4
6
Order By: Relevance
“…This was established in a reactor type anode with a packed bed of similar granular electrode material. Kaku et al (2008) were also not able to detect decreased CH 4 emissions from Plant-MFCs in closed circuit in a rice field. On the other hand, it was shown that a closed circuit MFC was able to release 10 times less methane…”
Section: Current Producing Metabolism Precedes Methanogenic Metabolismmentioning
confidence: 82%
See 3 more Smart Citations
“…This was established in a reactor type anode with a packed bed of similar granular electrode material. Kaku et al (2008) were also not able to detect decreased CH 4 emissions from Plant-MFCs in closed circuit in a rice field. On the other hand, it was shown that a closed circuit MFC was able to release 10 times less methane…”
Section: Current Producing Metabolism Precedes Methanogenic Metabolismmentioning
confidence: 82%
“…Kaku et al (2008) were not able to show lower CH 4 emissions in closed circuit operation of a Plant-MFC during a field trial in a rice paddy. In this work the results of a microcosm study are presented in which rice plants were grown in vermiculite with a BES in the rhizosphere.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Recently proof of principle was delivered of renewable electricity generation via living higher plants in MFCs (Strik et al 2008a;De Schamphelaire et al 2008;Kaku et al 2008). Herein, the living plant is photosynthesizing and releasing a part of the produced organic materials via its roots into the root surroundings.…”
Section: Introductionmentioning
confidence: 99%